Cephalometrıc Evaluatıon Of The Effects Of Elactıc Bıte-Block Applıance In The Treatments Of Class Iı Dıv I Malocclusıons - Nejat Erverdi; Gökhan Özkan (Galenos Yayinevi, 1994)
The study was designed to evaluate the efficiency of EBB appliance on Class II Division I malocclusion cases. A total of 50 CI. II div. I cases were taken from clinical in take. Thirty of them were treated with EBB appliance and 20 were as control group, no treatment was applied to them. Patients characteristics were -Class II div. I malocclusion, - Retrognathic mandible, -Horizontal growth pattern, -Being in active growth period. Measurements were obtained from laterel cephalograms which were taken at the begining and right after the appliance removal. The measurements were evaluated statisticaly. The results were as follows: The sagital forward growth potential of the maxilla were retarded and the mandibular forward growth was stimulated. Upper molars were distalized and moved closes to the palatal plane. Lower molars erupted in the mesio-occlusal direction. Vertical dimension increased due to clock wise rotation of the mandible. Upper incisors uprighted and intruted. Lower incisors were moved lingualy and intruded. Overjet and over bite decreased.